Pendampingan strategi Pemasaran melalui Pengenalan dan Pengoperasian Media Sosial bagi Pelaku Usaha Kerajianan Gerabah di Desa Sukarara - Hamzani, Hamzani; Septa, Maulana (Lembaga Publikasi Ilmiah Nusantara, 2025)
Sukarara Village is known as one of the centers of pottery craftsmanship, renowned for its high artistic and cultural value. However, most pottery entrepreneurs in the village still rely on conventional marketing methods, which limits their market reach and is less effective in today's digital era. This community service activity aims to assist these entrepreneurs in developing marketing strategies through the introduction and use of social media as a means of promotion and market expansion. The methods used include outreach, hands-on training, and intensive mentoring on platforms such as Instagram, Facebook, and WhatsApp Business. The activities also cover the creation of engaging promotional content, social media account management, and a basic understanding of digital market analysis. The results show an increase in participants' understanding and skills in using social media to support product marketing. Several entrepreneurs have begun to independently create and manage their business social media accounts, as well as enhance online interaction with consumers. Another positive impact observed is the growing motivation among entrepreneurs to innovate and adapt to technological developments. This activity proves that social media-based marketing strategies are highly relevant and effective in driving the growth of local MSMEs, particularly in the handicraft sector. Going forward, continued mentoring is expected to ensure sustainability and optimal business development.